Development of local wisdom-based IPAS teaching modules integrated with the Pancasila student profile in elementary school - Aisa Nikmah Rahmatih; Asri Fauzi; Ida Ermiana; Nurkhaerat Alimuddin (MASI Mandiri Edukasi, 2026)
Natural and Social Sciences (IPAS) learning in elementary schools is often delivered in a theoretical manner and remains insufficiently connected to students’ real-life experiences. In contrast, the Merdeka Curriculum emphasizes contextual learning and character development by integrating Pancasila Student Profile values. This highlights the need for teaching materials that support conceptual understanding while reflecting local cultural contexts. This study aimed to develop a local wisdom–based Natural and Social Sciences teaching module integrated with the Pancasila Student Profile for elementary school students. The module was developed using the ADDIE model and implemented with 182 students in Grades 3, 4, and 5. Data were collected through expert validation, teacher response questionnaires, and student learning outcomes. The results indicated that the developed module achieved a high level of validity (76.62) and was considered highly practical by teachers. Statistical analysis also confirmed that the module was significantly effective in improving students’ learning outcomes. The implementation produced average scores of 81.41 in Grade 3, 81.35 in Grade 4, and 80.40 in Grade 5. These findings demonstrate that integrating local wisdom into teaching modules can enhance contextual learning while strengthening students’ cultural identity. Therefore, the module offers a relevant instructional resource to support the effective implementation of the Merdeka Curriculum in elementary education.